Hubungan Tingkat Pengetahuan Dengan Upaya Pencegahan Kekambuhan Gastritis Di Wilayah Kerja Puskesmas Gatak Sukoharjo - Khusna, Luluk Ulyatul; , Fahrun Nur, S.Kep.,Ns., M.Kes; , Faizah Betty R, A.Kep., S.Kep.,M.Kes (2016)
Gastritis is a digestive disorder that is most commonly encountered in clinical practice. In 2014, gastritisincluded inthe fivediseases inSukoharjo. In work area health Gatak Sukoharjo, increased cases ofgastritisfromyear to year.To avoid the occurrence of gastritis required for prevention efforts with attention to good eating habits everyday. There are several factors that can influence the occurrence of gastritis among which the knowledge and efforts to prevent gastritis. The aim of research to determine the relationship of the level of knowledge of gastritis with prevention of recurrence in patients with gastritis in Puskesmas Gatak Sukoharjo. The method used is descriptive correlational cross-sectional design. The patient population aged 20-44 years in the clinic Gatak Sukoharjo numbering 231, were taken a sample of 70 people with proportional random sampling technique. Independent variables such as the level of knowledge of gastritis while the dependent variable gastritis relapse prevention efforts, the instrument used by the questioner. Data analysis techniques with Spearman rank correlation analysis. The results showed that most respondents have a level of knowledge about gastritik high, the majority of respondents in the prevention of recurrence gastritik quite good and there was a significant association with gastritis level of knowledge about prevention of recurrence in patients with gastritis in Puskesmas Gatak Sukoharjo. Gastritis are advised for patients to maintain their health by maintaining a regular diet and avoid things that can cause gastritis Keywords: Level of knowledge, efforts to prevent recurrence, gastritis